(untitled) (Journal of Economic Research & Business Administration, 2015)
Currently, the market economy requires structural maneuvers and substantial reallocation of labor across sectors over the country. The emergence of unemployment in a given scale necessitated state regulation of employment in accordance with modern requirements. It should be the interaction of all the levers of government and instruments of a market economy, social partnership between the main actors of the labor market, including encouraging the state to employers who create new jobs, promote professional and territorial mobility of labor by providing information on job opportunities, employer and employment services in other regions.The solution to these problems can not be done in isolation from the structural and investment policy, social programs, policies, income, etc. However, the state regulation of employment of an active influence on the socio-economic transformation in the country, as the rise in unemployment may be one of the most significant factors of economic stagnation and social instability in society.